Comprehensive Hydrodynamic Analysis of Oscillating Flapping Mechanism for Enhanced Wave Energy Converter Technology - Aldi Anggara, Rizki; Julian, James; Wahyuni, Fitri; Purba, Riki Hendra (Universitas Muhammadiyah Metro, 2025)
The comprehensive utilization of renewable energy stands as a national priority within Indonesia's strategic framework aimed at achieving the net zero emissions target by 2060. Indonesia, a nation in which nearly 70% of its territory is comprised of oceans, possesses significant potential in wave energy as a renewable energy source. This sector presents promising opportunities for development and investment. This study focuses on the three-dimensional hydrodynamic study of Wave Energy Converter (WEC) technology based on oscillating flapping through a numerical approach. The findings of the characteristic test demonstrate that the oscillating flapping device exhibits a response characterized by a deviation in the oscillating tilt angle. The direct impact of ocean waves causes the flap to shift from its equilibrium position and continuously move back and forth with a particular frequency. The dynamics working on this device show a correlation between wave input and the response that occurs. The response parameters, including maximum angular deviation, average speed, and torque, have a similar trend to changes in wave period. The influence of ocean wave activity is observed to increase within the low wave period zone up to a designated period threshold. Overall, the oscillating flapping device demonstrates enhanced performance in low wave conditions. The average maximum output power is capable of reaching 1.5 Watts on A1, 3.5 Watts on A2, and 4.5 Watts on A3.